(untitled) (Bioagro, 2024)
The INIFAP, through seed production, provides corn hybrids to meet the demand of farmers in the different agroecological zones of the country. Therefore, it is essential to generate technologies to identify environments for the optimal development of their progenitors. The objective of the study was to identify optimum seeding ratios for yield and seed quality in hybrids H-384A and H-385A. The research was conducted in the November 2012-May 2013 cycle in the states of Colima (Coquimatlan) and Nayarit (Bahía de Banderas and Villa Hidalgo). A completely randomized design in factorial arrangement with four replications was used. Male and female flowering, plant and ear height, percentage of rachis (RAC) and seed (SEE), yield (YIE), thousand seed weight (TSW), number of seeds per kilogram, germination percentage (Germ) and hectoliter seed weight (PH) were evaluated. Significant differences (P≤0,01 and P≤0,05) for genotypes and environments were observed for most variables. As for environment×proportion revealed significance (P≤0,05) in RAC and SEE. It was found that the hybrid H-384A, outperforms H-385A in the parameters of SEE, PH, TSW, Germ and YIE. The best environment for seed production was in Nayarit (Villa Hidalgo) with the sowing ratio 4:2, however, it is suggested to consider the origin of the parents for greater efficiency of seed production lots.